Pelatihan Perakitan Robot Line Follower Pada Siswa SMAN 6 Metro Lampung - Al Barra Harahap; Listra Yehezkiel Ginting; Nike Dwi Grevika Drantantiyas; Amrina Mustaqim; Hesti Wahyu Handani (CV. Multi Kreasi Media, 2025)
Robotic system is a combination of various elements working together to control the behaviour, movement, and decisions made by the robot. The components are made of hardwares, softwares, user interface, communication, mechanical structure, energy source, and safety. Using this technology, students of SMAN 6 Metro can stay up to date with recent technologies, and can implement it to solve problems as necessary. The aim for this community service is to introduce knowledge about the utility of robotic systems related to the components of the system and its implementation. The target of this event is students of SMAN 6 Metro and also the university students attending this event. Introduction starts with definition of robotic systems, components of a robot, methodology, and implementation. As a result of this event, we find that the knowledge of the students of SMAN 6 Metro seem to be improving significantly. The experience proved to be a fascinating experience for the students involved.